DESIGNING OF NOISE POLLUTION MEASURES FOR A MILITARY AIRFIELD - Tomáš HOIKA; Zbyšek KORECKI (Scientific Journal of Silesian University of Technology. Series Transport)
This article discusses the possibilities of reducing noise pollution in the vicinity of a selected airport, with an emphasis on practical measures. The proposed procedures, which are routinely employed at commercial airports, would be ineffective or financially unsustainable under the circumstances of the military airports. The objective at military airports is not to maximise capacity, as at civil airports, where the desire to increase capacity is primarily related to profit. The primary objective for military airports is to perform defined tasks, which may include pilot training, search and rescue exercises and combat training. The main measures proposed to reduce noise pollution in the vicinity of the villages are changes in departure and arrival routes, the splitting of night operations into two parts and the introduction of a new article in the AIP and Airport Regulations prohibiting air operations over and in close proximity to the villages nearby. Finally, it is stressed that a significant reduction in noise will only be possible with the support of changes in legislation or above-standard financial investment by the airport operator.